Good corporate governance analysis of financial performance at Pt bank sulselbar - RINI FAUZIAH RAHMAN (International Journal of Multidisciplinary Research and Studies, 2023)
This research intends to examine the impact of effective corporate governance, including the presence of independent commissioners and audit committees, on the financial performance of PT Bank SULSELBAR. The investigation took place within the premises of PT Bank SULSELBAR and utilized quantitative research techniques. The study encompassed all the subsidiaries of PT Bank SULSELBAR, with a purposive sampling approach resulting in the selection of 5 branches as the study's sample. The theoretical frameworks underpinning this research are agency theory, signaling theory, and attribution theory. To conduct the study, secondary data from the official websites of the respective companies were employed. The data were subsequently subjected to Regression Analysis utilizing SPSS software. The outcomes of the analysis indicated that, when taken individually, the influence of independent commissioners and audit committees on financial performance was not statistically significant